Dukungan Sosial dengan Burnout pada Guru di Masa Pandemi Covid-19 - Warella, Veren Wendy; Ratnawati, Tri (Faculty of Psychology, Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract. This study aims to look at social support with teacher Burnout during the Covid 19 pandemic. Burnout is a condition in which individuals experience physical, mental and emotional suffering that occurs, due to stress which increases a long period of time in situations that require adequate emotional interaction. high. In this review article, the researcher wants to focus on social support with teacher Burnout during the Covid 19 pandemic. The data taken from this study are related journals that discuss Burnout in its increase with social support. The criteria of the journal include: Journals in English and or Indonesian, explaining Burnout and social support and analyzing this research.